Beneficial effects of caffeic acid phenethyl ester on formaldehyde-induced learning and memory disabilities: A labyrinth test performance study - Türko?lu, Asli Özdem; Sarsilmaz, Mustafa; Ögetürk, Murat; Kuş, Ilter; Songur, Ahmet (My University, 2008)
Purpose: In this study, it was aimed to investigate the efficacy of caffeic acid phenethyl ester (CAPE) on formaldehyde (HCHO)-induced learning and memory changes in rats. Material and Methods: For this purpose, labyrinth test was performed on 21 male Wistar rats. These animals were divided into three equal groups. All groups underwent training period in the labyrinth test. At the end of this period, control rats were injected intraperitoneally with ethanol; the rats in HCHO group were injected intraperitoneally with formaldehyde, and the rats in HCHO+CAPE group were injected with CAPE along with formaldehyde. All animals, within injection period, were subjected to labyrinth test again. The time spent by each rat in reaching the target was recorded and statistically evaluated using one-way variance analysis (ANOVA) and two-way ANOVA for repeated measures. Results: Formaldehyde was observed to cause defects in learning and memory, and changes in behavior in rats. The time used by the HCHO-exposed rats in reaching the target was longer than that of control rats. This negative effect of HCHO exposure was partially alleviated by CAPE administration. Conclusion: In view of the present findings, it is suggested that caffeic acid phenethyl ester exerts beneficial effects against formaldehyde toxicity.
Keywords: Caffeic acid phenethyl ester; Formaldehyde; Neurotoxicity; Rat